RESPON PERTUMBUHAN DAN HASIL TANAMAN TERONG TERHADAP PENGGUNAAN MEDIA TANAM DAN DOSIS PUPUK ORGANIK - NI KOMANG BUDIYANI; NI PUTU EKA APRIASTUTI; I MADE MAHADI DWIPRADNYANA (Universitas Mahasaraswati K. Mataram, 2023)
Eggplant is a vegetable group that is in great demand by various groups due to its delicious taste and high nutritional content and complete composition. The purpose of this study was to determine the response of eggplant growth and yield to the use of growing media and doses of organic fertilizers. The study used a randomized block design (RBD) with 2 factors, namely the planting medium which consisted of 4 levels, namely M0, M1, M2, M3 and the dose of organic fertilizer consisted of 4 levels, namely P0, P1, P2, P3.The results showed that the planting medium affected several parameters, including plant height (M1), number of leaves (M2), number of fruit (M3), and fruit weight (M2). And the organic fertilizer dose treatment significantly affected the parameters of the number of leaves (P2) and the number of fruits (P3).